Exploring the real estate and insurance industry in Metro Manila: Implications of moonlighting and work motivation to employee agility as moderated by self-efficacy and Work from Home - Chua, Jen Elle M. (Animo Repository, 2022)
The gig economy has been growing exponentially over the past decade, yet there is little known research on the implications of multiple job holders for employees and businesses alike. The study aims to determine the relationship between moonlighting and work motivation to work agility as moderated by work from home and self-efficacy in the real estate and insurance industry. This study utilized a quantitative research design, particularly, causal-explanatory, descriptive and correlational. Through an online questionnaire, 151 Metro Manila-based real estate and insurance professionals were surveyed. Supplementing this was a qualitative approach by interviewing four (4) subject matter experts. Analysis of data was conducted through descriptive statistics, Pearson’s correlation, linear and multiple regression, analysis of variance, pattern matching, and moderated regression. Findings revealed no moderating effect of working from home and self-efficacy on moonlighting and work motivation on employee agility. This implies that work-from-home and self-efficacy should be improved by real estate and insurance industries to capitalize on moonlighting behavior and improve work motivation to have employee agility. It is recommended that the real estate industry increase its work-from-home setup by incorporating CRM technologies and investing in virtual property showcases. Insurance management can boost motivation via certifications and proper rewards.